THE USE OF POWER POINT LEARNING MEDIA IMPROVES THE LEARNING OUTCOMES OF AL-QURAN - Taufiq, Ahmad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
PTK Research Classroom Action Research was conducted at MTs Riyadlus Sholihin Rejing-Tiris-Probolinggo in the subjects of Al-Qur'an Hadith class VII B which amounted to 24 female students. The purpose of the study is to improve student learning outcomes. The focus of this research is improvement in the use of learning media. Learning improvement is carried out in two improvement cycles, from these two improvement cycles researchers design learning plans using power point media. In pre-cycle learning activities, there were 52.17% of students who did not complete or scored below 70 (KKM) and only 47.83% of students had scored 70 and above. In the first cycle, there were 34.78% of students who were incomplete and 65.22% of students who had completed. In this first cycle of learning improvement, student learning completeness increased by 14.72% from learning carried out in the pre-cycle. In this second cycle of learning improvement, the increase in learning outcomes has increased significantly and completeness has reached 95.65%. The results of the implementation of the second cycle of learning have improved well and have reached the expected completeness criteria with the level of completeness of student learning outcomes reaching 95.65%.